Complete Genome Sequence of the Probiotic Enterococcus faecalis Symbioflor 1 Clone DSM 16431 - Fritzenwanker, Moritz (American Society for Microbiology, 2013)
Here, we report the complete and annotated genome sequence of the probiotic Enterococcus faecalis Symbioflor 1 clone DSM 16431, included in a commercial probiotic product used for more than 50 years without any reports of infection. This sequence will provide new insights into the biology of this nonpathogenic and probiotic microorganism.